2021
DOI: 10.2166/wpt.2021.104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HRT and seasons on the performance of pilot-scale horizontal subsurface flow constructed wetland to treat rural wastewater

Abstract: To find the effect of Hydraulic Retention Time (HRT) and seasons on the performance of horizontal subsurface flow constructed wetland (HSSF CW) in treating rural wastewater, a pilot scale unit 2.5 m × 0.4 m × 0.3 m size bed planted with a Typha latifolia and Phragmites australis was operated for a 12-month duration. During the study 2, 4, 6, 8, and 10 days of HRT were maintained in winter, summer, and rainy seasons. The removal efficiency obtained was ranges from 62.09 to 87.23% for Chemical Oxygen Demand, 69.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…The removal efficiency (%) for N (nitrite-N and nitrate-N) ranged between 7 to 50% for control, 11 to 94.74% for FTWs with Canna, 41 to 94.74% for FTWs with Typha, 50 to 94.74% for FTWs mixed with both Canna and Typha sp. In the present research work, the nitrogen removal efficiency was in the moderate to a higher range which is in line with previous studies performed using FTWs with plants (Garcia Chance et al 2020, Wang and Sample 2014, White and Cousins 2013, Boonsong and Chansiri 2008, Ghosh and Gopal 2010, Minakshi et al 2021, Toet et al 2005, Shruthi and Shivashankara 2022. Mean percentage removal efficiency for N (NO 2 -and NO 3 --N) was 29.5, 61.1, 69.2 and 71.8% for control, FTWs with Canna (CW1), Typha (CW2) and mixed (CW3), respectively (Figs.…”
Section: Nitrogen Removalsupporting
confidence: 92%
See 2 more Smart Citations
“…The removal efficiency (%) for N (nitrite-N and nitrate-N) ranged between 7 to 50% for control, 11 to 94.74% for FTWs with Canna, 41 to 94.74% for FTWs with Typha, 50 to 94.74% for FTWs mixed with both Canna and Typha sp. In the present research work, the nitrogen removal efficiency was in the moderate to a higher range which is in line with previous studies performed using FTWs with plants (Garcia Chance et al 2020, Wang and Sample 2014, White and Cousins 2013, Boonsong and Chansiri 2008, Ghosh and Gopal 2010, Minakshi et al 2021, Toet et al 2005, Shruthi and Shivashankara 2022. Mean percentage removal efficiency for N (NO 2 -and NO 3 --N) was 29.5, 61.1, 69.2 and 71.8% for control, FTWs with Canna (CW1), Typha (CW2) and mixed (CW3), respectively (Figs.…”
Section: Nitrogen Removalsupporting
confidence: 92%
“…The performance of FTWs largely depends on HRT. Previous studies showed that increasing HRT shows increased pollutant and nutrient removal but to a certain limits (Ghosh and Gopal 2010, Minakshi et al 2021, Toet et al 2005, Shruthi and Shivashankara 2022. The present study was conducted for 5 months (from January 2022 to May 2022) in total 11 batches.…”
Section: Hydraulic Retention Time (Hrt)mentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding water temperature, the result was contrary to that of the aforementioned parameters, since in both types of systems -planted and unvegetated systems -, the values decreased by an average of 5.5°C and 4.6 ºC, respectively. This performance coincides with the pilot-scale horizontal CW reported by Shruthi & Shivashankara, (2022), where the wastewater temperature decreased in 1.2 °C after passing through the system.…”
Section: Dissolved Oxygen Ph and Water Temperaturesupporting
confidence: 88%
“…In a recent pilot-scale study on the treatment of synthetic wastewater using a vertical subsurface flow CW vegetated with two plants namely Typha latifolia and Phragmites australis, the pollutant (e.g., COD) removal efficiency constantly increased with the rise of HRT from 2 days (69.4%), 4 days (77.6%), 6 days (86.3%), 8 days (86.4%) and 10 days (88.8%) (Shruthi and Shivashankara, 2021b). Another work from the same research group using a horizontal subsurface flow CW run under similar operational conditions (e.g., HRT) also reported a similar relationship between HRT and pollutant removal, i.e., COD removal increased by 65.0, 74.4, 82.8, 86.1 and 88.3% with increase of HRT by 2, 4, 6, 8 and 10 days, respectively (Shruthi and Shivashankara, 2021a). Badhe et al (2014) explored the performance of a free surface, up-flow CW planted with Typha latifolia for removal COD, ammonia and phosphate under two different HRTs (1.5 and 2.5 days), and the pollutant removal efficiency was slightly higher at HRT of 1.5 days (COD: 65.02%, ammonia: 4.9% and phosphate: 11.1%) than 2.5 days (COD: 55.5%, ammonia: 4% and phosphate: 11%).…”
Section: Factors Impacting Pollutants Removal Performance Of Construc...mentioning
confidence: 57%